"We Roll our Sleeves up and get to Work!": Portraits of Collective Action and Neighborhood Change in Atlanta's West End. Issue 6 (November 2022) - Foell, Andrew; Foster, Kirk A.
Collective action is one strategy urban neighborhood residents use to address community issues. However, collective action dynamics in rapidly changing urban neighborhoods are not well understood. This study used photovoice to examine perspectives on collective action and neighborhood change among residents of an urban neighborhood experiencing redevelopment in Atlanta, Georgia, USA. Residents indicated that place attachment motivated and reinforced participation in collective action efforts to address neighborhood issues and to reconstruct narratives that challenged place stigmatization. Findings suggest that residents have heterogeneous perspectives about neighborhood change and local development, and simultaneously balance desires for neighborhood improvement with concerns about displacement, gentrification, and equitable development.